Differences in echocardiographic characteristics of functional mitral regurgitation in ischaemic versus idiopathic dilated cardiomyopathy: a pilot study. - Papadopoulou, K; Giannakoulas, G; Karvounis, H; Dalamanga, E; Karamitsos, T; Parcharidou, D; Damvopoulou, E; Efthimiadis, G; Styliadis, I; Parcharidis, G (2009)
INTRODUCTION: Functional mitral regurgitation (FMR) is a common complication in patients with ischaemic (ICM) or idiopathic dilated cardiomyopathy (DCM), as a consequence of left ventricular (LV) remodelling. The aim of this study was to elucidate the differences in FMR between patients with ICM and DCM utilising conventional and tissue Doppler echocardiography. METHODS: We studied 21 patients with ICM and 17 with DCM using conventional and tissue Doppler echocardiography. The severity of FMR was assessed quantitatively and by the PISA method. The 2 groups were similar in terms of NYHA class, LV ejection fraction and pharmacological treatment. RESULTS: Patients with ICM had higher pulmonary artery systolic pressures (48 +/- 16 vs. 38 +/- 10 mmHg, p=0.04), more severe FMR as assessed by colour Doppler (1.9 +/- 0.9 vs. 1.1 +/- 0.5, p=0.006), and a larger effective regurgitant orifice (0.17 +/- 0.07 vs. 0.1 +/- 0.05 cm(2), p=0.003) and tenting area (2.3 +/- 0.8 vs. 1.7 +/- 0.7 cm(2), p=0.02). In addition, ICM subjects had lower mitral annular systolic (Sm 2.3 +/- 0.8 vs. 3.4 +/- 0.9 cm/s, p<0.001) and diastolic (Em 2.5 +/- 1 vs. 3.8 +/- 1.5 cm/s, p=0.005; Am 3.1 +/- 1.4 vs. 4.3 +/- 1.7 cm/s, p=0.02) myocardial velocities, and a higher ratio of early transmitral filling velocity to early mitral annular diastolic velocity (LV E/Em 42 +/- 29 vs. 22.7 +/- 7.6, p=0.008) compared to DCM patients. Systolic and diastolic mitral annular velocities were significantly correlated with effective regurgitant orifice. Tenting area >1.27 cm(2) exhibited the highest sensitivity and regurgitant volume >24 ml the highest specificity for predicting ischaemic aetiology of LV dysfunction. However, only age and Sm were independent predictors of the diagnosis of ICM rather than DCM. CONCLUSIONS: Mitral apparatus deformity, incomplete closure of mitral leaflets and global remodelling are more prominent in patients with ICM and lead to more severe FMR than in patients with DCM.